Mediasi komitmen organisasi pada pengaruh gaya kepemimpinan terhadap kinerja karyawan Hotel di Yogyakarta - Hananto, Kombang (Journal of Management and Digital Business, 2025)
This study aims to examine whether organizational commitment mediates the effect of leadership style on subordinates' job performance. The research was conducted in hotels in Yogyakarta. This study is based on a quantitative descriptive approach using the partial least square-structural equation model (PLS-SEM) to test its hypothesis model. The model was tested with 187 respondents. The results show that organizational commitment mediates the effect of transformational leadership style on subordinates' performance in the hospitality industry. It was also found that transformational, transactional, and laissez-faire leadership styles significantly affect subordinates' performance. The implication is that hotel leaders should recognize appropriate actions and consider suitable leadership behaviours to enhance job performance, especially organizational commitment. Furthermore, organizational commitment also directly and significantly impacts job performance.